ANALISA KEPUASAN PENGGUNA APLIKASI E-XAMP EDITOR SEBAGAI APLIKASI UJIAN SEKOLAH BERBASIS KOMPUTER DI SMKN 3 PARIAMAN MENGGUNAKAN METODE END USER COMPUTING SATISFACTION (EUCS) YANG DIPERLUAS - Kurnia Anesa; Zulhendra Zulhendra; Denny Kurniadi (Universitas Negeri Padang, 2017)
This study aims to evaluate the satisfaction of System e-Xamp Editor users in SMKN 3 Pariaman. The evaluation was conducted based on the perception of the end user by using End-User Computing Satisfaction (EUCS) model. EUCS Model has 6 factors i.e. content, accuracy, format, ease of use timeliness and flexibility, these 6 factors used as independent variable to evaluate e-Xamp editor user satisfaction in SMKN 3 Pariaman. This research using questionnaire as a primary data as well as scientific journals, reference books as secondary data. This research uses validity test, reliability test, normality test and linear regression analysis as methods of data analysis. The results showed that 6 factors of EUCS model affects 61% of e-Xamp editor user satisfaction. Content affects 6,15% of e-Xamp editor user satisfaction, timeliness affects 15,76% of e-Xamp editor user satisfaction, ease of use affects 15,36% of e-Xamp editor user satisfaction, format affects 5,52% of e-Xamp editor user sastisfaction, accuracy affects 2,5% of e-Xamp editor user satisfaction and flexibility affects 6,4% of e-Xamp editor user satisfaction. Kata kunci: User Satisfaction, e-Xamp editor, End-User ComputingSatisfaction (EUCS)